2015
DOI: 10.3109/17435390.2015.1102981
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose exposure of silica nanoparticles induces cardiac dysfunction via neutrophil-mediated inflammation and cardiac contraction in zebrafish embryos

Abstract: The toxicity mechanism of nanoparticles on vertebrate cardiovascular system is still unclear, especially on the low-level exposure. This study was to explore the toxic effect and mechanisms of low-dose exposure of silica nanoparticles (SiNPs) on cardiac function in zebrafish embryos via the intravenous microinjection. The dosage of SiNPs was based on the no observed adverse effect level (NOAEL) of malformation assessment in zebrafish embryos. The mainly cardiac toxicity phenotypes induced by SiNPs were pericar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 45 publications
5
53
1
Order By: Relevance
“…Increased level of hsp90aa1.2 was observed in zebrafish exposed to site H4 water, consistent with the results that the expression levels of various hsp genes are increased in fish exposed to environmental pollutants, such as microcystin-LR [43], heavy metals [44] and industrial effluents [45]. It was reported that silica nanoparticles induced cardiac dysfunction of zebrafish embryo and inhibited the cardiac muscle contraction via affecting related genes, such as ATPase-related genes and regulatory gene tnnc1a for cardiac troponin C [46], and these genes were also altered in the liver of zebrafish exposed to the sampled Hun River water.…”
Section: Discussionsupporting
confidence: 74%
“…Increased level of hsp90aa1.2 was observed in zebrafish exposed to site H4 water, consistent with the results that the expression levels of various hsp genes are increased in fish exposed to environmental pollutants, such as microcystin-LR [43], heavy metals [44] and industrial effluents [45]. It was reported that silica nanoparticles induced cardiac dysfunction of zebrafish embryo and inhibited the cardiac muscle contraction via affecting related genes, such as ATPase-related genes and regulatory gene tnnc1a for cardiac troponin C [46], and these genes were also altered in the liver of zebrafish exposed to the sampled Hun River water.…”
Section: Discussionsupporting
confidence: 74%
“…The cell suspensions were centrifuged at 1,500 rpm for 5 minutes. In total, 5 mL cell lysate containing HNO 3 and H 2 O 2 (3:1) was added in cell pellets. Then, the silicon content in the lysis solution was detected using ICP-AES.…”
Section: Lactate Dehydrogenase Release Assaymentioning
confidence: 99%
“…Specifically, due to many advantages, 2 In recent years, the adverse effects of SiNPs on cardiovascular toxicity and atherosclerosis development have gained attention, and studies demonstrated a clear cardiovascular health risk associated with SiNPs exposure. 3,4 Vascular endothelia line the inner surface of blood vessels, and provide an essential structural and biological barrier to maintain vascular function and homeostasis. Endothelial dysfunction is now hypothesized to be a dominant mechanism in the development of cardiovascular diseases, including atherosclerosis and ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, there was no or minimal damage to kidney when SiNPs were administered in vivo. 40,49,51 It had been reported that SiNPs induced cardiotoxicity to zebrafish embryo because these particles inhibited angiogenesis and disturbed heart formation and development; 52 neutrophil-mediated cardiac inflammation 53 was assumed to be the cause. However, no definite cardiac injury was noted in the studies 40,49,51 of mature mice.…”
mentioning
confidence: 99%